Modular tool for dairy cow ration optimization: spreadsheet based approach - Žgajnar, Jaka; Kavčič, Stane (Economics of Agriculture, 2010)
Paper presents developed spreadsheet tool for dairy cow ration formulation It is constructed on the basis of two linked modules in MS Excel platform, merging common linear programming and weighted goal programming model with penalty functions. The frst module estimates the least-cost magnitude that might be expected. Obtained result enters into the second module as goal that should be met as close as possible. The tool was tested at two different values of preferential weights for dairy cow with 20 kg daily milk yield. Obtained results confrm benefts of applied methodology since one is enabled to formulate least-cost ration and simultaneously overcome major drawbacks of LP approach. Besides fne tuning of set goals rational violence is enabled through penalty function system. As result calculated ration is more effcient both from economic and nutritive point of view.